2011
DOI: 10.12693/aphyspola.119.387
|View full text |Cite
|
Sign up to set email alerts
|

Barium Strontium Bismuth Niobate Layered Perovskites: Dielectric, Impedance and Electrical Modulus Characteristics

Abstract: SrBi 2 Nb 2 O 9 (SBN) is a bismuth layered perovskite compound, due to its relatively high Curie temperature, has potential application as high ceramic transducer. Also, it is an attractive ferroelectric material that is being considered in non-volatile random access memory cells. Present article describes preparation, dielectric, impedance and modulus characteristics. Temperature and frequency dependence of dielectric permittivity, impedance and electric modulus of barium strontium bismuth niobate (Ba 0.1 Sr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…To better understand these phenomena, The complex dielectric constant as a function of the frequency ω in accordance with the Jonscher's power law is given by the following expression 9,18 :…”
Section: Resultsmentioning
confidence: 99%
“…To better understand these phenomena, The complex dielectric constant as a function of the frequency ω in accordance with the Jonscher's power law is given by the following expression 9,18 :…”
Section: Resultsmentioning
confidence: 99%
“…It can be concluded that real impedance Z' is independent of frequency and doping content (x) beyond 1kHz. The higher Z' values at low frequencies in samples with 10 and 20% tin is because of low mass space charge from PNR dominant microstructure of 10 and 20% tin doped SSBLN compositions [27][28][29], also seen in Fig.4. Fig.7(b) shows a very interesting variation of Z"…”
Section: Fig 4 Dielectric Dispersion Of Tin-doped Ssbln Compositionsmentioning
confidence: 69%
“…A similar description of dielectric relaxation is represented in the case of an electrical modulus but the maximum M (ν) is shifted to a higher frequency in respect of the ε (ν) maximum [40]. the source of the potential barrier is related to the Cu ions, which segregate themselves into the grain boundaries.…”
Section: Measurements' Techniquesmentioning
confidence: 99%